Visual–spatial training efficacy in children affected by migraine without aura: a multicenter study - Precenzano F (Dove Medical Press, 2017)
Francesco Precenzano,1,* Maria Ruberto,2,* Lucia Parisi,3 Margherita Salerno,4 Agata Maltese,3 Beatrice Gallai,5 Rosa Marotta,6 Serena Marianna Lavano,7 Francesco Lavano,6 Michele Roccella3 1Clinic of Child and Adolescent Neuropsychiatry, Headache Center for Children and Adolescent. Department of Mental and Physical Health and Preventive Medicine, Università degli Studi della Campania Luigi Vanvitelli, 2Department of Medical-Surgical and Dental Specialties, Università degli Studi della Campania Luigi Vanvitelli, Naples, 3Department of Psychological, Pedagogical and Educational Sciences, 4Sciences for Mother and Child Health Promotion, University of Palermo, Palermo, 5Department of Surgical and Biomedical Sciences, University of Perugia, Perugia, 6Department of Medical and Surgery Sciences, 7Department of Health Sciences, University “Magna Graecia”, Catanzaro, Italy *These authors contributed equally to this work Abstract: Routinely in the clinical practice, children affected by migraine without aura (MwA) tend to exhibit severe and persistent difficulties within cognitive processes such as attention, memory, and visual–motor integration (VMI) skills. The aim of this study was to assess the visual–spatial and visual–motor abilities among a sample of children with MwA and the effects of a specific computerized training. The study population was composed of 84 patients affected by MwA (39 girls and 45 boys; mean age: 8.91±2.46 years), and they were randomly divided into two groups (group A and group B) comparable for age (P=0.581), gender (P=0.826), socioeconomic status (SES), migraine frequency (P=0.415), and intensity (P=0.323). At baseline (T0), the two groups were comparable for movement assessment battery for children (M-ABC) and VMI performances. After 6 months of treatment (T1), group A showed lower scores in the dexterity item of M-ABC test (P<0.001) and higher scores in M-ABC global performance centile (P<0.001) and total (P<0.001), visual (P=0.017), and motor (P<0.001) tasks of VMI test than group B. Moreover, at T1, group A showed higher scores in total (P<0.001) and motor (P<0.001) tasks of VMI test and in M-ABC global performance centile (P<0.001) and lower scores in the dexterity item of M-ABC test (P<0.001) than at T0. Group B showed, at T1, performances comparable to T0 for all evaluations. As reported by recent studies about alteration MwA among children in motor abilities, our study confirmed these difficulties and the efficacy of a specific software training, suggesting a new rehabilitative proposal in childhood. Keywords: migraine without aura, visual–motor integration, visual–motor training skills